Pre-fattening of crossbred dairy bulls under grazing with glycine (Neonotonia wightii) and tropical grasses with rumen activator supplement - D?az, Aslam; Castillo, Emilio; Martin, Pedro C.; Hern?ndez, Jorge Luis (Cuban Journal of Agricultural Science, 2013)
The productive performance of 24 crossbred dairy males (5/8 Holstein x 3/8 Zebu), of 330 ? 31 d of age and liveweight (LW) from 134.02 to 228.28 kg was assessed. The animals grazed on an association of glycine (Neonotonia wightii) and natural pasture during the rainy season (160 d). The system of 6 ha was divided into eight paddocks. The occupation and resting times were of 5 and 35 d, respectively, with stocking rate of four animals/ha. An amount of 1.50 kg of activator supplement of the ruminal fermentation (15.20 % of CP and 9.33 MJ kg of DM-1 of ME was offered. A grazing pressure of 12.90 kg DM per each 100 kg of LW was maintained. The daily mean gain (DMG) was of 589.13 g of LW per animal. The system favored the fulfillment of the ingestion capacity and the CP requirements, while the ME was slightly below the requirements (1.25 MJ) for the real DMG obtained. Besides, it allowed the inclusion of a great number of animals to the fattening. These results corroborate the necessity of working with lower animal stocking rate or with supplements with higher energy content to improve the use of the pastures CP, obtain higher DMG of LW and reduce the incorporation age of the animals to the fattening. Key words: bovinos, herbaceous legumes, pre-fattening, productive performance.